Information Flows on the Wholesale Food Market in Poland - Nowakowska-Grunt, J. (Электронное моделирование, 2008)
The problem of information flows organization on the food goods market in Poland is presented. Information flows are analyzed on the wholesaler market and the example of logistics centre is used – Wielkopolska Gildia Rolno-Ogrodnicza S.A. The paper is considering the issues of information system improvement necessity because of its usage in researched object. Представлена задача организации информационных потоков на продуктoвом рынке Польши. Дан анализ информационных потоков на оптовом рынке и приведен пример центра логистики Wielkopolska Gildia Rolno-Ogrodnicza S.A. Рассмотрены проблемы усовершенствования информационной системы для использования ее в исследуемом объекте. Наведено задачу організації інформаційних потоків на продуктовому ринку Польщі. Дано аналіз інформаційних потоків на оптовому ринку і наведено приклад центру логістики Wielkopolska Gildia Rolno-Ogrodnicza S.A. Розглянуто проблеми удосконалення інформаційної системи для використання ії у досліджуваному об’єкті.